1994
DOI: 10.1148/radiology.192.2.8029430
|View full text |Cite
|
Sign up to set email alerts
|

Renal vascular resistance in diabetic nephropathy: duplex Doppler US evaluation.

Abstract: Doppler indexes reflect increased RVR in diabetic nephropathy and correlate with laboratory and clinical parameters, but RI and PI measurements offer no advantages over these parameters to predict disease progress or in patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 0 publications
6
27
0
1
Order By: Relevance
“…. 11 years) and higher blood pressure, and present a higher rate of renal failure requiring dialysis (71% con RI Z 1.0) [29,30]. All these clinical data correlate with the level of renal arteriolosclerosis (nephroangiosclerosis) (Fig.…”
Section: Diabetic Nephropathymentioning
confidence: 83%
“…. 11 years) and higher blood pressure, and present a higher rate of renal failure requiring dialysis (71% con RI Z 1.0) [29,30]. All these clinical data correlate with the level of renal arteriolosclerosis (nephroangiosclerosis) (Fig.…”
Section: Diabetic Nephropathymentioning
confidence: 83%
“…Only a few studies describing the application of Doppler sonography in the evaluation of intrarenal hemodynamic abnormalities in DN have been published so far, and most of these were performed in adults with type 1 or type 2 diabetes mellitus. 1,8,10,[23][24][25][26][27] Data investigating relationship between RI and early clinical stage of DN in children and adolescents with diabetes are still lacking, and the correlation between increased intrarenal RI and altered renal hemodynamics remains unclear. Recently, Okten et al 26 reported that renal Doppler sonography was not useful for the prediction and early detection of DN in children.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of the intrarenal RI have been demonstrated both in diabetic patients with detectable nephropathy [8,9], and in patients with normal renal function [7].…”
Section: Discussionmentioning
confidence: 99%